Breaking the Magic Code: Finding the Pattern of Goodkind’s Fantasy Fiction Wizard’s First Rule - Desti Ilmianti Saleh (Passage, 2014)
The present study entitled Breaking the Magic Code: Finding the Pattern of Goodkind’s Fantasy Fiction Wizard’s First Rule aims at identifying the pattern of the story through analyzing the fantasemes and the ways the story constructs the logic of the secondary world. Utilizing a qualitative research particularly descriptive method, the study adopts Nikolajeva’s (1988) fantasy theory. The study found that the fantasy story construction is presented through combination of fantasemes. From the analysis of the fantasemes it is clear that the story utilizes a pattern linear to common fantasy fiction, however it also creates a new pattern. Similar to other fantasy stories, this story has a character traveling and leaving home, challenged and helped, performing a task and gaining triumph. The differences are in the absence of primary world which is replaced by heterotopias. The story constructs the logic of the secondary world through following magic laws, namely limitation and consistency.Keywords: Fantasy, Fantasemes, The Magic Space, The Magic Time, The Magic Passage, The Magic Impact, The Magic Law